2011
DOI: 10.2460/ajvr.72.8.1118
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of transplantation of autologous bone marrow stromal cells into the cerebrospinal fluid for treatment of chronic spinal cord injury in dogs

Abstract: Injection of BMSCs into the CSF caused no complications and could have beneficial effects on pelvic limb locomotion in dogs with chronic spinal cord injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
46
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 38 publications
1
46
0
1
Order By: Relevance
“…To the best of our knowledge, there have been only a few reports on the number of days until canine BMSCs reach confluency or the number of canine BMSCs collected in one passage [7,12]. In the present study, canine BMSCs grew to confluency at about 10 days, and approximately 3.8 × 10 6 BMSCs were collected per 2 ml of bone marrow in one passage.…”
mentioning
confidence: 63%
See 4 more Smart Citations
“…To the best of our knowledge, there have been only a few reports on the number of days until canine BMSCs reach confluency or the number of canine BMSCs collected in one passage [7,12]. In the present study, canine BMSCs grew to confluency at about 10 days, and approximately 3.8 × 10 6 BMSCs were collected per 2 ml of bone marrow in one passage.…”
mentioning
confidence: 63%
“…Some studies have shown that canine BMSCs can differentiate into neuron-like cells expressing mature neuronal markers [5,7,8]. For these reasons, our laboratory is currently investigating BMSCs for use in spinal cord regenerative therapy in dogs.Recently, the experimental study and clinical trial of regenerative therapy for SCI using autologous BMSCs also been performed in dogs [5,12]. Surprisingly, there have been almost no reports regarding basic research on canine BMSCs, although this is very important for the clinical application of canine BMSCs.…”
mentioning
confidence: 99%
See 3 more Smart Citations